Caused to believe : the Doubting Thomas story at the climax of John's Christological narrative - Bonney, William (Biblical interpretation series, 2002)
This work is a literary study of John's gospel focusing upon the doubting Thomas story's role as its climax. It analyzes the Thomas episode in light of the roles played by the characters Jesus encounters throughout the gospel.